Targeting Histone Deacetylases: A Novel Approach in Parkinson’s Disease - Sorabh Sharma; Rajeev Taliyan (Parkinson's Disease)
The worldwide prevalence of movement disorders is increasing day by day. Parkinson’s disease (PD) is the most common movement disorder. In general, the clinical manifestations of PD result from dysfunction of the basal ganglia. Although the exact underlying mechanisms leading to neural cell death in this disease remains unknown, the genetic causes are often established. Indeed, it is becoming increasingly evident that chromatin acetylation status can be impaired during the neurological disease conditions. The acetylation and deacetylation of histone proteins are carried out by opposing actions of histone acetyltransferases (HATs) and histone deacetylases (HDACs), respectively. In the recent past, studies with HDAC inhibitors result in beneficial effects in both in vivo and in vitro models of PD. Various clinical trials have also been initiated to investigate the possible therapeutic potential of HDAC inhibitors in patients suffering from PD. The possible mechanisms assigned for these neuroprotective actions of HDAC inhibitors involve transcriptional activation of neuronal survival genes and maintenance of histone acetylation homeostasis, both of which have been shown to be dysregulated in PD. In this review, the authors have discussed the putative role of HDAC inhibitors in PD and associated abnormalities and suggest new directions for future research in PD.